"I Don't Believe in Leading a Life of My Own, I Lead His Life": A Qualitative Investigation of Difficulties Experienced by Informal Caregivers of Stroke Survivors Experiencing Depressive and Anxious Symptoms. Issue 4 (8th August 2018) - Woodford, Joanne; Farrand, Paul; Watkins, Edward R.; LLewellyn, David J.
ABSTRACT: Objectives: Health and social care services are increasingly reliant on informal caregivers to provide long-term support to stroke survivors. However, caregiving is associated with elevated levels of depression and anxiety in the caregiver that may also negatively impact stroke survivor recovery. This qualitative study aims to understand the specific difficulties experienced by caregivers experiencing elevated symptoms of anxiety and depression. Methods: Nineteen semi-structured interviews were conducted with caregivers experiencing elevated levels of depression and anxiety, with a thematic analysis approach adopted for analysis.Results : Analysis revealed three main themes: Difficulties adapting to the caring role; Uncertainty; and Lack of support. Conclusions: Caregivers experienced significant difficulties adapting to changes and losses associated with becoming a caregiver, such as giving up roles and goals of importance and value. Such difficulties persisted into the long-term and were coupled with feelings of hopelessness and worry. Difficulties were further exacerbated by social isolation, lack of information and poor long-term health and social care support. Clinical Implications: A greater understanding of difficulties experienced by depressed and anxious caregivers may inform the development of psychological support targeting difficulties unique to the caring role. Improving caregiver mental health may also result in health benefits for stroke survivors themselves.